Pengaruh Kualitas Produk Dan Harga Terhadap Keputusan Pembelian Pelanggan Produk Skincare Pada Marketplace Shopee Di Depok - Ariandi, Fajri; Rahman, Arif; Arista, Roynaldi; Utama, Dani Chandra (CV. ULIL ALBAB CORP, 2024)
This research aims to examine the influence of product quality and price on skincare customers' purchasing decisions at the Shopee market place in Depok. This research uses a quantitative descriptive method by distributing questionnaires via Google Form with purposive sampling, namely Shopee users as an online shopping platform for skincare consumers in Depok. The sample was taken using a purposive sampling method of 120 respondents. In analyzing the research data, SPSS 26 was used to calculate the results of the Multiple Linear Regression variable test, t test, F test, and determination analysis. The results of this research show that based on the t test, product quality and price have a positive influence on skincare customers' purchasing decisions at the Shopee market place in Depok. Based on the results of the F Test, product quality and price together have a significant influence on skincare customers' purchasing decisions at the Shopee market place in Depok. Based on the results of multiple regression analysis, product quality and price influence skincare customers' purchasing decisions at the Shopee market place in Depok only by 72% while the remaining 28% is influenced by other variables not examined in this research.